PHARMACEUTICAL STANDARDIZATION OF SHATPALA GANDHAKA CHURNA - Reddy, *Hema; Sridurga, Ch (International Journal of Ayurveda and Pharma Research, 2018)
Rasa oushadis are the potent Ayurvedic preparations mainly containing metals and minerals. These Oushadis possess wide range of therapeutic efficacy and are considered superior because of their qualities like small dose, quick action, palatability and longer shelf life. Shatpala Gandhaka churna is an important Rasa oushadi described in Vaidya chintamani- Kushtha prakaranam indicated for all types of Kushtha, Grahani, Gulma, Mandagni. Shatpala Gandhaka Churna contains Shuddha Gandhaka, Shuddha Bhallataka, Shuddha Chitrakamula twak, Triphala, Vidanga, Trikatu, Trijataka, Chanaka, and Jeeraka. The main pharmaceutical procedures adopted in this study are Shodhana, Churna nirmana and preparation of capsule of Shatpala Gandhaka Churna. The specific pharmaceutical blend of these contents can result in a more effective formulation. Till now, no research work has been carried out to standardize this formulation. Therefore the present study has been planned to standardize the method of preparation of Shatpala Gandhaka churna according to the method explained in the classical literature.